Metal(loid) levels in biological matrices from human populations exposed to mining contamination-Panasqueira Mine (Portugal) - Coelho, Patrícia (2019)
Mining activities may affect the health of miners and communities living near mining sites, and these health effects may persist even when the mine is abandoned. During mining processes various toxic wastes are produced and released into the surrounding environment, resulting in contamination of air, drinking water, rivers, plants, and soils. In a geochemical sampling campaign undertaken in the Panasqueira Mine area of central Portugal, an anomalous distribution of several metals and arsenic (As) was identified in various environmental media. Several potentially harmful elements, including As, cadmium (Cd), chromium (Cr), manganese (Mn), nickel (Ni), lead (Pb), and selenium (Se), were quantified in blood, urine, hair, and nails (toe and finger) from a group of individuals living near the Panasqueira Mine who were environmentally and occupationally exposed. A group with similar demographic characteristics without known exposure to mining activities was also compared. Genotoxicity was evaluated by means of T-cell receptor (TCR) mutation assay, and percentages of different lymphocyte subsets were selected as immunotoxicity biomarkers. Inductively coupled plasma-mass spectrometry (ICP-MS) and inductively coupled plasma-atomic emission spectrometry (ICP-AES) analysis showed elevated levels of As, Cd, Cr, Mn, and Pb in all biological samples taken from populations living close to the mine compared to controls. Genotoxic and immunotoxic differences were also observed. The results provide evidence of an elevated potential risk to the health of populations, with environmental and occupational exposures resulting from mining activities. Further, the results emphasize the need to implement preventive measures, remediation, and rehabilitation plans for the region.